A proposal for the management of health surveillance and monitoring procedures in relation to the risks posed by SARS-COV-2 to hospital and nursing home workers, based on strategies implemented in the facilities of the Fondazione Opera San Camillo - Saretto, Gianni; Bozzi, Carla (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2021)
This paper describes how the health surveillance protocols adopted in hospitals and nursing homes have changed in response to the spread of SARS-CoV-2 and its risks. These changes concern assessments that must be performed with urgency, to detect potential cases and symptoms that may indicate contagion and to protect vulnerable and hypersensitive workers. Besides, these changes have been implemented in order to regulate how the appointed occupational physician should perform everyday tasks, particularly in regard to preventive visits, periodic visits, office visits, and visits meant to authorize one’s return to the workplace. This paper recommends that both preventive visits and periodic visits should include rapid antigen swab tests to screen for SARS-CoV-2 (which, if positive, should be confirmed by molecular tests) and serologic tests to detect IgG SARS-CoV-2 antibodies. Since this phase involves great risks for healthcare facilities, this paper proposes that swab testing should be performed every month and that serologic testing should be performed every three months (depending on whether the first test detects the presence of IgG antibodies). By combining antigen and molecular swab tests, healthcare professionals can diagnose workers with SARS-CoV-2 and identify positive asymptomatic cases. Because of its costs and its long turnaround times for results, molecular swab testing is recommended only when one needs to confirm a positive antigen swab test result. Serologic testing should be used alongside swab testing, to acquire data concerning the immunity of workers.